The effects of IL-27 and IL-35 gene variation and expression levels on the susceptibility and clinical manifestations of pulmonary tuberculosis - Gao, Lei; Xiong, Yan-Jun; Liang, Ya-Xue; Huang, Peng-Fei; Liu, Shuang; Xiao, Yu; Huang, Qian; Wang, Hua; Wu, Hui-Mei (Frontiers in Immunology, 2024)
Inflammatory cytokines have crucial roles in the pathogenesis of tuberculosis (TB), and interleukin (IL)-27, IL-35 play pro-inflammatory and anti-inflammatory effects in many diseases, including infectious diseases. Therefore, we evaluated the relationship between IL-27, IL-35 genes polymorphism, expression levels and pulmonary TB (PTB) susceptibility. Nine single nucleotide polymorphisms (SNPs) in IL-27 gene (rs181206, rs153109, rs17855750), IL-35 gene (rs4740, rs428253, rs9807813, rs2243123, rs2243135, rs568408) were genotyped by SNPscan technique in 497 patients with PTB and 501 controls. There was no significant difference regarding the genotype and allele frequencies of above SNPs in IL-27, IL-35 genes between PTB patients and controls. Haplotype analysis showed that the frequency of GAC haplotype in IL-35 gene was significantly decreased in PTB patients when compared to controls (P = 0.036). Stratified analysis suggested that the frequency of IL-27 rs17855750 GG genotype was significantly increased in PTB patients with fever.Moreover, the lower frequency of IL-35 rs568408 GA genotype was associated with drug-induced liver injury in PTB patients. IL-35 rs428253 GC genotype, as well as rs4740 AA genotype and A allele, showed significant relationships with hypoproteinemia in PTB patients. When compared with controls, the IL-27 level was significantly increased in PTB patients. Taken together, IL-35 gene variation might contribute to a protective role on the susceptibility to PTB, and IL-27, IL-35 genes polymorphisms were associated with several clinical manifestations of PTB patients.